Réponses

  • Utilisateur Brainly
2014-09-13T14:11:33+02:00
C= (1 + 1/2) - (5/4 + 1/3)
C= (2/2 + 1/2) - (15/12 + 4/12)
C= 3/2 - 19/12
C= 18/12 - 19/12
C= - 1/12

B= 5/11 x (3 + 5/2)
B= 5/11 x (6/2 + 5/2)
B= 5/11 x 11/2
B= 5/2 (on simplifie par 11)
Merci beaucoup de m'avoir aider :)
De rien! =)
2014-09-13T14:13:42+02:00
C = ( 1 + 1/2) - (5/4 + 1/3)
C = (1 x 2 / 1 x 2 + 1/2) - (5 x 3 / 4 x 3 + 1 x 4 / 3 x 4)
C = (2/2 + 1/2) - (15/12 + 4/12)
C = 3/2 - 19/12
C = 3 x 6 / 2 x 6 - 19/12
C = 18/12 - 19/12
C = - 1/12

B = 5/11 x (3 + 5/2)
B = 5/11 x (3 x 2 / 1 x 2 + 5/2)
B = 5/11 x (6/2 + 5/2)
B = 5/11 x 11/2
B = 55/22
B = 11 x 5 / 11 x 2
B = 5/2